Advances in prodrug design - Távora de Albuquerque Silva, Antonio [UNESP]; Chin, Chung Man [UNESP]; Castro, Lúcia Fioravanti [UNESP]; Carvalho Güido, Rafael Victorio [UNESP]; Ferreira, Elizabeth Igne (Bentham Science Publishers, 2005)
The background of prodrug design is presented herein as the basis for introducing new and advanced latent systems, taking into account mainly the versatility of polymers and other macromolecules as carriers. PDEPT (Polymer-Directed Enzyme Prodrug Therapy); PELT (Polymer-Enzyme Liposome Therapy); CDS (Chemical Delivery System); ADEPT(Antibody-Directed Enzyme Prodrug Therapy); GDEPT/VDEPT (Gene-Directed Enzyme Prodrug Therapy/Virus-Directed Enzyme Prodrug Therapy); ODDS (Osteotropic Drug Delivery System) and LEAPT (Lectin-directed enzyme-activated prodrug therapy) are briefly described and some examples are given. © 2005 Bentham Science Publishers Ltd.
Keywords: Latent advanced systems; Macromolecules carriers; Prodrug design; Selective delivery systems; aminosalicylic acid; ampicillin; antiinflammatory agent; antileishmanial agent; antimalarial agent; antineoplastic agent; bisphosphonic acid derivative; cytochrome P450; diclofenac; doxorubicin; flucytosine; ibuprofen; irinotecan; isoniazid; ketoprofen; mevinolin; mitomycin; nitrofural; paclitaxel derivative; photosensitizing agent; prodrug; salazosulfapyridine; tacrolimus; testosterone derivative; tiaprofenic acid; tolmetin; trigonelline; tryptamine derivative; unindexed drug; antibody directed enzyme prodrug therapy; bactericidal activity; binding affinity; blood brain barrier; Chagas disease; diarrhea; drug absorption; drug activation; drug design; drug distribution; drug identification; drug receptor binding; drug screening; drug selectivity; drug stability; drug structure; drug synthesis; drug targeting; drug transformation; gastrointestinal toxicity; gene expression; human; hypercholesterolemia; in vivo study; macromolecule; malaria; minimum inhibitory concentration; nephrotoxicity; organoleptic property; osteoporosis; review; rheumatoid arthritis; structure activity relation; structure analysis; tuberculosis; ulcerative colitis; Animals; Antibodies; Drug Carriers; Drug Delivery Systems; Drug Design; Gene Therapy; Humans; Lectins; Macromolecular Substances; Osteoporosis; Prodrugs; Viruses